Microscale receiver operating characteristic analysis of micrometastasis recognition using activatable fluorescent probes indicates leukocyte imaging as a critical factor to enhance accuracy - Spring, Bryan Q. (Society of Photo-Optical Instrumentation Engineers, 2014)
Molecular-targeted probes are emerging with applications for optical biopsy of cancer. An underexplored potential clinical use of these probes is to monitor residual cancer micrometastases that escape cytoreductive surgery and chemotherapy. Here, we show that leukocytes, or white blood cells, residing in nontumor tissues—as well as those infiltrating micrometastatic lesions—uptake cancer cell-targeted, activatable immunoconjugates nonspecifically, which limits the accuracy and resolution of micrometastasis recognition using these probes. Receiver operating characteristic analysis of freshly excised tissues from a mouse model of peritoneal carcinomatosis suggests that dual-color imaging, adding an immunostain for leukocytes, offers promise for enabling accurate recognition of single cancer cells. Our results indicate that leukocyte identification improves micrometastasis recognition sensitivity and specificity from 92 to 93%—for multicellular metastases [Formula: see text] to 30 μm in size—to 98 to 99.9% for resolving metastases as small as a single cell.